Walnut Supplementation Restores the SIRT1-FoxO3a-MnSOD/Catalase Axis in the Heart, Promotes an Anti-Inflammatory Fatty Acid Profile in Plasma, and Lowers Blood Pressure on Fructose-Rich Diet. (22nd April 2021) - Bošković, Maja; Živković, Maja; Korićanac, Goran; Stanišić, Jelena; Zec, Manja; Krga, Irena; Stanković, Aleksandra
Abstract : The benefits of walnut ( Juglans regia ) consumption for metabolic health are known, but the molecular background underlying their putative antioxidant and anti-inflammatory/immunomodulatory effects is underexplored. We assessed that walnut supplementation (6 weeks) reverted unfavorable changes of the SIRT1/FoxO3a/MnSOD/catalase axis in the heart induced by fructose-rich diet (FRD). Intriguingly, Nox4 was increased by both FRD and walnut supplementation. FRD increased the cytosolic fraction and decreased the nuclear fraction of the uniquely elucidated ChREBP in the heart. The ChREBP nuclear fraction was decreased in control rats subjected to walnuts. In addition, walnut consumption was associated with a reduction in systolic BP in FRD and a decrease in fatty acid AA/EPA and AA/DHA ratios in plasma. In summary, the protective effect of walnut supplementation was detected in male rats following the fructose-induced decrease in antioxidative/anti-inflammatory capacity of cardiac tissue and increase in plasma predictors of low-grade inflammation. The current results provide a novel insight into the relationship between nutrients, cellular energy homeostasis, and the modulators of inflammatory/immune response in metabolic syndrome, emphasizing the heart and highlighting a track for translation into nutrition and dietary therapeutic approaches against metabolic disease.